1994
DOI: 10.1101/gad.8.18.2162
|View full text |Cite
|
Sign up to set email alerts
|

Mutation of the SPS1-encoded protein kinase of Saccharomyces cerevisiae leads to defects in transcription and morphology during spore formation.

Abstract: During spoiulation of Saccharomyces cerevisiae, meiosis is followed by encapsulation of haploid nuclei within multilayered spore walls. Completion of the late events of the sporulation program requires the SPSl gene. This developmentally regulated gene, which is expressed as cells are nearing the end of meiosis, encodes a protein with homology to serine/threonine protein kinases. The catalytic domain of Spsl is 44% identical to the kinase domain of yeast Ste20, a protein involved in the pheromone-induced signa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
132
1
1

Year Published

1995
1995
1997
1997

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(138 citation statements)
references
References 77 publications
(86 reference statements)
4
132
1
1
Order By: Relevance
“…The speci®city of the antiserum was veri®ed, since immunoprecipitation was blocked when the antiserum was preincubated with recombinant GST-KHS ( Figure 3a). This antiserum was also able to speci®cally immunoprecipitate a 95 kD protein from metaboli- (Katz et al, 1994;Creasy and Cherno , 1995;Cvrckova et al, 1995;Leberer et al, 1992;Ramer and Davis, 1993;Freisen et al, 1994;Marcus et al, 1995;Bagrodia et al, 1995;Knaus et al, 1995;Manser et al, 1994Martin et al, 1995;Ottilie et al, 1995). Catalytic domains are boxed.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The speci®city of the antiserum was veri®ed, since immunoprecipitation was blocked when the antiserum was preincubated with recombinant GST-KHS ( Figure 3a). This antiserum was also able to speci®cally immunoprecipitate a 95 kD protein from metaboli- (Katz et al, 1994;Creasy and Cherno , 1995;Cvrckova et al, 1995;Leberer et al, 1992;Ramer and Davis, 1993;Freisen et al, 1994;Marcus et al, 1995;Bagrodia et al, 1995;Knaus et al, 1995;Manser et al, 1994Martin et al, 1995;Ottilie et al, 1995). Catalytic domains are boxed.…”
Section: Resultsmentioning
confidence: 99%
“…Epistatically, it is positioned immediately downstream of the heterotrimeric G protein (encoded by STE4, STE18, and GPA) and upstream of the module of kinases including STE11, STE7, and FUS3 or KSS1. SPS1 is required in the MAP kinase pathway regulating spore formation (Freisen et al, 1994). Its position in the cascade is known only to be upstream of the MAP kinase SMK1 (Krisak et al, 1994).…”
Section: Discussionmentioning
confidence: 99%
“…HAtagged p38 was immunoprecipitated using anti-HA tag antibody and its activity was tested by solid-phase kinase assay using GST-CREBP1 as a substrate (Herskowitz, 1995). The phenotype of homozygous Sps1 mutants is similar to that of cells with a disrupted smk1 gene, which encodes a protein with homology to MAP kinases (Friesen et al, 1994;Krisak et al, 1994), suggesting that Sps1 and Smk1 may be components of the MAPK pathway involved in spore cell formation. The fact that YSK1 is structurally related to Sps1 and Ste20 prompted us to investigate whether YSK1 could complement null mutants for the Ste20 and Sps1 loci.…”
Section: Discussionmentioning
confidence: 99%
“…A homology search using the Smith-Waterman algorithm (Smith and Waterman, 1981) on the MPsearch network service program revealed that YSK1 shows signi®cant sequence identify to the kinase domains of the Ste20-related kinases (Table 2) MST1 (57% identity), a human protein kinase homologous to Ste20, possibly negatively regulated by phosphorylation ; Sps1 (53% identity), an upstream kinase of the budding yeast MAPK pathway that is involved in spore wall formation (Friesen et al, 1994;Krisak et al, 1994); GCK (52% identity), which is characteristically expressed in the germinal center of the lymphoid follicles and is involved in the regulation of the JNK/ SAPK pathway (Katz et al, 1994;Pombo et al, 1995); Ste20 (46% identity), which is activated upon stimulation of the heterotrimeric G-protein-coupled pheromone receptor and leads to the activation of the Fus3/Kss1 subgroup of yeast MAPKs (Leberer et al, 1992); PAK (44% identity), which is the ®rst identi®ed mammalian relative of Ste20 and activated by the binding of the ras-related small G-proteins Rac1 and Cdc42 (Manser et al, 1994); Cla4 (44% identity), which is involved in budding and cytokinesis in yeast, and interacts with Cdc42 (Cvrckova et al, 1995; and Shk1 (41% identity), a Ste20 homologue of ®ssion yeast, whose interaction with Cdc42 is required for normal cell morphology and mating (Marcus et al, 1995) (Figure 2b). In particular, the overall structures of YSK1, MST1, Sps1, and GCK are very similar.…”
Section: Ysk1 Is Homologous To Ste20-related Kinasesmentioning
confidence: 99%
See 1 more Smart Citation